Effects of different fermentation methods on the quality of sour cowpea - SUN Yu, ZHOU Zhugui, LIU Jian, XIN Ming, LI Changbao, FENG Jinqing, LI Jieming, LI Tianyu, YE Dongqing, LING Dongning (Zhongguo niangzao)
Fresh cowpeas (Vigna unguiculata (Linn.) Walp.) were fermented by three ways: spontaneous fermentation (CK group), inoculation of commercial strains (CS group), inoculation of self-screening direct vat set starter (DVS group). The total acidity, pH of the broth total during fermentation and salinity, nitrite, amino acid nitrogen, free amino acids, lactic acid bacteria count, color difference, sensory quality and textural characteristics of finished fermented cowpeas were determined, to analysis the effect of the fermentation methods on the quality of sour cowpeas. The results showed that during fermentation, the total acidity of DVS group increased faster than those in both CK and CS group from 1-6 d. The pH of CS and DVS group decreased faster than CK group and the CS group reached the lowest on 7 d, followed by DVS group. The total bacteria count in DVS group was 33.86% and 42.31% higher than that in CK and CS group respectively on 7 d. After fermentation, the DVS group had the lowest salinity, nitrite, b* values, and the highest amino acid nitrogen, free amino acids, lactic acid bacteria count, sensory score, hardness, viscosity, gelatinousness and chewiness, but L* values, a* values and elasticity were not significantly different from the other fermentation methods (P>0.05). By comprehensive analysis, the DVS group not only had faster fermentation initiation and higher acid tolerance, but the finished product also had better overall quality.